ANALISIS TINGKAT KESEHATAN BANK DENGAN MENGGUNAKAN METODE RGEC PADA PT BANK RAKYAT INDONESIA TBK PERIODE 2017-2020 - Sela Selvia; Sukma Febrianti (Jurnal Ekonomi STIEP, 2022)
This study aims to determine the level of bank health in PT Bank Rakyat Indonesia Tbk period 2017-2020, using RGEC (Risk Profile, Good Corporate Governance, Earnings and Capital) method. This type of research is descriptive quantitative. This study uses a method based on the assessment of the calculation of each indicator. Risk Profile assessment using non-performing loan (NPL) and Loan To Deposit Ratio (LDR) financial ratio received a healthy category, although in the LDR ratio in the period 2017-2019 got a fairly healthy category. Good Corporate Governance assessment using Self Assessment results as a whole get a healthy category, although in 2017 it falls into the category of very healthy. Earnings valuation using Return On Assets (ROA) and Net Interest Margin (NIM) got a very healthy category. Capital Assessment using Capital Adequacy Ratio (CAR) gets a very healthy category. Based on the results of the analysis, it can be concluded that from 2017 to 2020 the health level of PT Bank Rakyat Indonesia Tbk was ranked composite 1 with the criteria "VERY HEALTHY".